answersLogoWhite

0

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed.

t+(3-2t)=4t+1

3-t=4t+1

2-t=4t

2=5t

last step is yours

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
ViviVivi
Your ride-or-die bestie who's seen you through every high and low.
Chat with Vivi
SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve

Add your answer:

Earn +20 pts
Q: T plus 3-2t equals 4t plus 1?
Write your answer...
Submit
Still have questions?
magnify glass
imp